2019
DOI: 10.21273/hortsci13543-18
|View full text |Cite
|
Sign up to set email alerts
|

Global Macadamia Science: Overview of the Special Section

Abstract: Macadamia is a rapidly developing global crop; however, limited cultivation history and size of the industry means many challenges remain to support sustained productivity and profitability of this industry. This paper summarizes oral and poster presentations, and subsequent papers included in this volume, delivered at the 2017 International Macadamia Research Symposium, held in Hilo, HI, in September of that year. This was the first international meeting of macadamia researchers since 1992. The 28 oral and se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 9 publications
(14 reference statements)
0
4
0
Order By: Relevance
“…Previous research has suggested that new generation (refers to distinct period of varietal development) macadamia varieties (NGMV) with enhanced yield potential and improved resilience to pests and diseases can elevate smallholder productivity [14,15]. These NGMVs are higher yielding (� 45 kg tree -1 year -1 ) than old generation varieties (OGMVs), which yield less than 30 kg tree -1 year -1 [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has suggested that new generation (refers to distinct period of varietal development) macadamia varieties (NGMV) with enhanced yield potential and improved resilience to pests and diseases can elevate smallholder productivity [14,15]. These NGMVs are higher yielding (� 45 kg tree -1 year -1 ) than old generation varieties (OGMVs), which yield less than 30 kg tree -1 year -1 [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Life 2021, 11, 1431 2 of 18 90% of China's total production comes from just Yunnan and Guangxi province [7]. The research knowledge related to breeding tools, nutrition management, disease management, processing methods, and product development is fundamental for the rapid devolvement of the macadamia oil industry around the world [8].…”
Section: Introductionmentioning
confidence: 99%
“…Macadamia is a genus in the Proteaceae family and grows naturally in the subtropical rainforest of eastern Australia (Hardner et al, 2019). Macadamia integrifolia , M .…”
Section: Introductionmentioning
confidence: 99%
“…Macadamia is a genus in the Proteaceae family and grows naturally in the subtropical rainforest of eastern Australia (Hardner et al, 2019). Macadamia integrifolia, M. tetraphylla, and their hybrids are cultivated for their high-value edible cream to white coloured nut in frost-free subtropical and tropical regions globally (Wallace & Walton, 2011).…”
Section: Introductionmentioning
confidence: 99%